Optimizing Productive Waqf: Challenges and Opportunities in Digitalization - Haliding, Safri; Putri, Nur Fathlia; Sapa, Nasrullah Bin (Jurnal Iqtisaduna, 2025)
This study explores the challenges and opportunities in the digitalization of productive waqf (Islamic endowment) to enhance its socio-economic impact in Indonesia. Through a descriptive literature review, the research examines how digital platforms, blockchain technology, and innovative financial models (e.g., cash waqf and crowdfunding) can optimize waqf management by improving transparency, accessibility, and efficiency. Key findings highlight Indonesia’s vast but underutilized waqf potential—estimated at IDR 180 trillion annually—while identifying barriers such as low digital literacy, regulatory gaps, and institutional capacity constraints. The study also discusses the role of Islamic social finance institutions in driving digital transformation, emphasizing the need for Sharia-compliant frameworks and community education. Case studies, including the National Cash Waqf Movement (GNWU), illustrate efforts to modernize waqf through technology. The paper concludes with recommendations for integrating digital tools, strengthening governance, and expanding outreach to marginalized regions, ultimately positioning waqf as a catalyst for sustainable development and financial inclusion in the Muslim-majority ASEAN context.